2018
DOI: 10.24969/hvt.2018.66
|View full text |Cite
|
Sign up to set email alerts
|

Primary detection of congenital heart diseases in the Kyrgyz Republic

Abstract: Objective: The aim of this paper is to understand the structure of congenital heart diseases (CHD) and the age of the first diagnosis in a population referred to specialized cardiac surgery center from different regions of Kyrgyz Republic. Methods: In 2017, 7213 people of different ages, from Kyrgyz Republic were examined by using transthoracic echocardiogram at cardiac surgery center aimed to detection of congenital heart disease Results: In total, 478 new patients with primary diagnosis of CHD were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A previous study of CHD in Kyrgyz Republic territory showed that only 14% of children had been diagnosed before discharge from the maternity hospital, and 86% of patients had a delayed diagnosis (8). The aim of study is evaluation of the scope of problem and gaining of novel statistical data on prevalence and detectability of CHD in various regions of Kyrgyz Republic Objectives: 1.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study of CHD in Kyrgyz Republic territory showed that only 14% of children had been diagnosed before discharge from the maternity hospital, and 86% of patients had a delayed diagnosis (8). The aim of study is evaluation of the scope of problem and gaining of novel statistical data on prevalence and detectability of CHD in various regions of Kyrgyz Republic Objectives: 1.…”
Section: Introductionmentioning
confidence: 99%